2009
DOI: 10.1159/000267277
|View full text |Cite
|
Sign up to set email alerts
|

Proportion, Risk Factors and Outcome of Lacunar Infarction: A Hospital-Based Study in a Chinese Population

et al.

Abstract: Background: There is scant information on the proportion, risk factors and outcome of lacunar infarction in China. Methods: Prospective registry data entered within 1 month after a first-ever stroke between March 2002 and March 2007 were used from 4 Chinese hospitals. Data regarding stroke risk factors and baseline characteristics were examined in a long-term follow-up. Case fatality, death and dependency, and stroke recurrence were assessed at 30, 90, 180 days and 1 year. Predictive factors for death at 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 52 publications
5
37
3
Order By: Relevance
“…Contrary to studies demonstrating an increased incidence of hypertension, diabetes, dyslipidaemia, smoking in Caucasians and Asians with LAC, our study did not reveal a significant excess of these risk factors [1,[5][6][7]. But a later systematic meta-analysis, reported that except for a marginal excess of hypertension in LAC, none of the other risk factors were predictive of either stroke subtype [11].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to studies demonstrating an increased incidence of hypertension, diabetes, dyslipidaemia, smoking in Caucasians and Asians with LAC, our study did not reveal a significant excess of these risk factors [1,[5][6][7]. But a later systematic meta-analysis, reported that except for a marginal excess of hypertension in LAC, none of the other risk factors were predictive of either stroke subtype [11].…”
Section: Discussioncontrasting
confidence: 99%
“…He proposed that lacunar strokes, asymptomatic small infarcts in striatocapsule are due to small vessel disease in the penetrating arteries and was the result of lipohyalinosis or atherosclerosis. Thus emerged the 'lacunar hypothesis' and these findings have led to studies on the two subtypes of stroke further enumerating that hypertension, diabetes and hyperlipidaemia are common in lacunar stroke with cardio embolism and large artery disease deemed less important [1,5]. But recent studies show that the risk factor profile is not different in stroke subtypes questioning the validity of lacunar hypothesis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, data for the impact of DM on outcomes of patients with ischemic stroke in China are limited and conflicting. Some studies have suggested that DM is a predictive factor for early-or long-term death after ischemic stroke, [15][16][17] but several studies have not. 12,18,19 The literature on the associations between DM and dependency and recurrent stroke in patients with ischemic stroke remains scarce.…”
mentioning
confidence: 99%
“…8 The overall registry project was approved by the Scientific Research Department of West China Hospital, Sichuan University, and procedures used to build the registry conformed to local and international standards of research ethics. West China Hospital is considered by some the largest single-site hospital in the world, with 4300 beds and >180 000 admissions in 2012.…”
Section: Patients and Evaluationmentioning
confidence: 99%